2015
DOI: 10.1542/peds.2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From Central Nervous System Acute Demyelination in Children

Abstract: Few prospective studies have systematically evaluated the extent of recovery from incident acquired demyelinating syndromes (ADS) of the central nervous system in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…For example, in one study that followed 59 patients with multiple sclerosis for a median of 5 years 11 months, 90% continued to have a normal neurological examination at final follow-up. 33 In a German study of 88 children with multiple sclerosis, the median scores on the Expanded Disability Status Scale were less than 1 at 2 years, 1.2 at 10 years, and 2.5 at 15 years. 29 A seminal paper that compared 394 patients with paediatric-onset multiple sclerosis and 1775 patients with adult-onset multiple sclerosis demonstrated that it took approximately 10 years longer for the patients with paediatric-onset disease to reach irreversible disability and secondary progression; however, they reached these landmarks at a biological age approximately 10 years younger than their counterparts with the adult-onset disease.…”
Section: Clinical Features and Disease Course: Does The Age Matter?mentioning
confidence: 96%
See 1 more Smart Citation
“…For example, in one study that followed 59 patients with multiple sclerosis for a median of 5 years 11 months, 90% continued to have a normal neurological examination at final follow-up. 33 In a German study of 88 children with multiple sclerosis, the median scores on the Expanded Disability Status Scale were less than 1 at 2 years, 1.2 at 10 years, and 2.5 at 15 years. 29 A seminal paper that compared 394 patients with paediatric-onset multiple sclerosis and 1775 patients with adult-onset multiple sclerosis demonstrated that it took approximately 10 years longer for the patients with paediatric-onset disease to reach irreversible disability and secondary progression; however, they reached these landmarks at a biological age approximately 10 years younger than their counterparts with the adult-onset disease.…”
Section: Clinical Features and Disease Course: Does The Age Matter?mentioning
confidence: 96%
“…This is postulated to be due to the greater plasticity of the developing brain and consequently a greater capacity for repair. For example, in one study that followed 59 patients with multiple sclerosis for a median of 5 years 11 months, 90% continued to have a normal neurological examination at final follow‐up . In a German study of 88 children with multiple sclerosis, the median scores on the Expanded Disability Status Scale were less than 1 at 2 years, 1.2 at 10 years, and 2.5 at 15 years .…”
Section: Clinical Features and Disease Course: Does The Age Matter?mentioning
confidence: 99%
“…21 Three additional studies have also shown complete recovery after a first attack of MS. Of 236 pediatric patients with MS from the United Kingdom and Iraq included in these 3 studies, 176 (75%) recovered fully after the first event. 6,10,22 African ancestry is often associated with increased MS severity in North American adult patients with MS.…”
Section: E1-e18mentioning
confidence: 97%
“…22 The tendency for very young patients with MS to manifest with polyfocal neurologic deficits and a high frequency of brainstem symptoms at onset were noted. Over the next 5 years, several key observations emerged: (1) children and adolescents experience relapsing neurologic deficits typical of adult-onset relapsingremitting MS but do not appear to experience primary progressive MS 23 ; (2) CSF analysis reveals the presence of intrathecal oligoclonal bands, a hallmark of MS in adults, in 60%-95% of pediatric patients, but less commonly in younger children 24 ; (3) over 95% of pediatric patients with MS recover well, in terms of physical functioning, from acute episodes early in their disease 25 ; (4) cognitive impairment occurs in approximately 30% of pediatric patients with MS [26][27][28][29][30][31][32] and correlates with MRI measures (reduced brain volume, altered resting state and functional connectivity, and reduced tissue integrity) [33][34][35][36][37][38] ; (5) pediatric patients with MS have higher relapse frequency in the first few years postonset, as compared to patients with adult-onset MS 39,40 ; and (6) time from first attack to secondary progressive MS (a stage of the disease characterized by progressive accrual of neurologic impairment not linked to discrete relapses) appears to take approximately 10 years longer in pediatric-onset patients, although the age at which such deficits appear occurs at a younger age than occurs in adult-onset MS.…”
Section: Pediatric Multiple Sclerosismentioning
confidence: 99%